Treatment of vitiligo with autologous cultured keratinocytes in 27 cases - Matsuzaki, Kyoichi (Springer Berlin Heidelberg, 2013)
BACKGROUND: Vitiligo is an acquired depigmentation of the skin characterized by white spots with well-defined margins, causing psychological stress in patients due to cosmetic concerns. We examined 27 patients who underwent vitiligo treatment using autologous cultured keratinocytes. METHODS: The study comprised 20 patients with segmental vitiligo and seven patients with generalized vitiligo, and they were followed up for at least 1 year postoperatively. In all 27 cases, topical steroid or ultraviolet therapy had been previously performed by dermatologists, but this treatment had been ineffective. The patients' vitiligo had stabilized. The patients were treated using keratinocytes obtained from primary culture using Green's techniques or from first passage. Dispase treatment was used to detach the stratified cultured epithelial sheets from their culture dishes. The detached sheets shrank to approximately one half to two thirds of their original size on the culture dish. After the recipient site was completely epithelialized, the skin was exposed to sunlight. RESULTS: For patients with segmental vitiligo, 12 had a good therapeutic outcome (90 % or more repigmentation) after the first surgery. This number increased to 14 when patients with multiple surgeries were included. There were six patients with fair outcomes (50–90 % repigmentation), and no patients with poor outcomes (50 % or less repigmentation). For patients with generalized vitiligo, no patients had a good outcome despite multiple surgeries. There were three patients with fair outcomes, and four patients with no change outcomes. CONCLUSIONS: Cultured keratinocyte grafting was a more effective treatment for segmental vitiligo than for generalized vitiligo. Level of Evidence: Level IV, therapeutic study.